The Influence of Ground Fly Ash on Cement Hydration and Mechanical Property of Mortar - Jingjing Feng; Jianwei Sun; Peiyu Yan (Advances in Civil Engineering, 2018)
In this study, the ground fly ash is made of ordinary grade I fly ash by grinding. Compared with grade I fly ash, the influence of ground fly ash on cement hydration and mechanical property of mortar was investigated. The results show that ground fly ash can improve the hydration of cement at all the ages compared with grade I fly ash, and not only does its pozzolanic reaction start earlier, but the reaction degree is higher and the speed is quicker. Before 3 days, the contribution of ground fly ash to the strength is mainly due to physical filling and microaggregate effect. After that, the contribution of pozzolanic effect to the strength becomes obvious and can significantly increase the compressive strength after 60 days and the flexural strength after 28 days. The ground fly ash is better than grade I fly ash to optimize the pore structure of hardened pastes. It can significantly reduce the number of harmful pores (>20 nm) and increase the number of harmless pores (<20 nm), which refines the pore structure and makes the structure denser.